Nosocomial transmission, adaption and clinical outcomes of carbapenem-resistant hypervirulent Klebsiella pneumoniae - Liu, Yanjun; Wang, Zhiqian; Jian, Zijuan; Liu, Peilin; Li, Yanming; Qin, Fang; Yan, Qun; Liu, Wenen (BMC microbiology, 2025)
Background Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-HvKp) poses a significant threat in healthcare settings. This study investigates the nosocomial transmission dynamics, adaptive phenotypes, and clinical outcomes of CR-HvKp with different evolutionary patterns. Methods A genomic analysis of 2,002 Klebsiella pneumoniae isolates collected from a major teaching hospital in China was performed to identify convergent isolates. Epidemiological features, including CR-HvKp nosocomial transmission, were assessed. Selected isolates underwent phenotypic testing to evaluate adaptive traits. Clinical outcomes were analyzed retrospectively using electronic medical records. Results A total of 127 CR-HvKp were characterized, with ST11-KL64 hv-CRKP (carbapenem resistant Klebsiella pneumoniae acquired hypervirulence) as the predominant sequence type. CR-HvKp exhibited diverse evolutionary patterns linked to nosocomial transmission, particularly in the ICU. ST11-KL64 hv-CRKP demonstrated robust transmission within ICU settings. Compared to CRKP, hv-CRKP showed enhanced in vitro competitiveness and superior immune evasion. CR-HvKp infections were significantly associated with higher mortality rates, especially involved in sepsis or septic shock ( P < 0.0001). Conclusion The ST11-KL64 hv-CRKP clonal complex is highly prevalent in CR-HvKp and demonstrates significant nosocomial transmission, particularly within ICU settings. Timely and effective sepsis management is critical to improving survival outcomes in CR-HvKp infections. Continuous genomic surveillance is imperative to control the spread of these pathogens.